Early systolic closure of the aortic valve. Issue 4 (October 1980) - Wong, P; Cotter, L; Gibson, D G
Abstract : Six patients with early systolic closure of the aortic valve are described with mitral regurgitation, double outlet right ventricle, left ventricular diverticulum, congestive cardiomyopathy, Eisenmenger ventricular septal defect, and aortic regurgitation with an aneurysmal ascending aorta, respectively. None had evidence of subaortic stenosis. Early sytolic closure of the aortic valve is thus not diagnostic of subvalvular aortic stenosis but is a non-specific finding.